SARS coronavirus-2 omicron variant transmission fractional order model with respiratory-specific and vaccination effects - Taohua Liu; Xiucao Yin; Qian Liu; Alphonse Houssou Hounye (Alexandria Engineering Journal, 2025)
Interventions to stop the spread of COVID-19 have incurred significant political and economic costs. In this context, we proposed an epidemiological pandemic model of COVID-19 with the omicron variant, which incorporates the use of respiratory-specific and supervised sampling by taking into account the link between the two and the quarantine approach. Next, the solution’s properties are investigated, and the next-generation matrix approach was used to determine the primary reproduction number R0=4.769e−4. Furthermore, we conducted a sensitivity analysis based on R0 parameters. The least squares curve fitting with Particle Swarm Optimization (PSO) techniques, are improved in this context, allowing for a more accurate determination of the model parameters. Partial Rank Correlation Coefficient Analysis(PRCC) was also conducted to see the impact of the parameters on the output of our model. Our numerical results reveal that the fractional models introduced in this study effectively encapsulate the dynamics of omicron, offering a robust tool for understanding and assessing the trajectory of the virus.